Potential association between M694V homozygous mutation in familial Mediterranean fever and eosinophilic intestinal inflammation: a pediatric case series - Dingulu, G.; Berrebi, D.; Martinez-Vinson, C.; Dumaine, C.; Melki, I.; Viala, J.; Valtuile, Z.; Vinit, C.; Hugot, J. P.; Meinzer, U. (Frontiers in Pediatrics, 2024)
Familial Mediterranean Fever (FMF) is the most common hereditary systemic auto-inflammatory disease. Digestive complaint is a common feature during FMF attacks. Nevertheless, digestive complaint in attack-free period has scarcely been studied. This retrospective monocentric study aimed to describe the clinical, histological and genetic features of pediatric patient with FMF who underwent endo-colonoscopy in this setting. Out of 115 patients with a diagnosis of FMF, 10 (8,7%) underwent endoscopy or colonoscopy. All displayed homozygote MEFV M694V mutation and presented chronic abdominal pain, iron deficiency and/or growth retardation. On the histological level, all patients displayed low-grade mucosal inflammation, characterized by a moderate eosinophilic infiltrate in the lamina propria sometimes associated to increased crypt apoptosis. The proportion of patients explored with endoscopy or colonoscopy was 0,4 patient per year in our center, compared to 5,7 patients per year nationwide. This study identified a specific intestinal phenotype that does not respond to criteria of classical Inflammatory Bowel Disease: Pediatric FMF pediatric patients with homozygous MEFV M694V, abdominal pain, iron deficiency and growth retardation should benefit from specialized gastroenterological advice.